Moderasi Madzhab dalam Pemikiran Fiqih dan Implikasinya terhadap Perkembangan Hukum Islam di Dunia Modern - Achmad, Kholiq; Makrum, Makrum; Anne Haerany, Anne Haerany; Fitri, Ahmad Asrof; Yasin, Raudlotul Firdaus Fatah (Jurnal Hukum Islam, 2025)
A moderate approach to schools of thought in fiqh is relevant for flexibly interpreting the Islamic law amidst the changing times and the challenges of globalization. This study discusses the role of moderation in schools of thought in fiqh and its implications for developing Islamic law in the modern world. By adopting a qualitative approach, collaborated with a conceptual, historical, and critical hermeneutic approach, this study explores the thoughts of contemporary scholars on the relevance of moderation in schools of thought and how it can enrich and adopt Islamic law in the dynamics of the modern society. Results show that moderation in schools of thought can encourage the creation of an inclusive, adaptive understanding of Islamic law and respond to the people’s needs in the era of globalization. However, the application of the school of thought in contemporary Islamic law encounters several limitations and complex structural challenges, including epistemological, sociological and political aspects. This finding highlights the importance of developing a moderate approach to Islamic law, which can strengthen the unity of Muslims amidst diversity and provide applicable and relevant legal solutions in the modern world.